A new Ptolemaic hypogeum with a Hadra vase at Tuna el-Gebel - Lembke, Katja (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2020)
While incineration was a form of punishment during the dynastic period, the ritual became more common in Ptolemaic times. Burninq of the corpse, however, was practised in Greek settlements only. As a consequence, the urns called Hadra vases were found to a great extent in Alexandria, but until now they were not recorded further south. The hypogeum with a Hadra vase dating to the early Ptolemaic Period excavated recently in Tuna el-Gebel by the Egyptian Ministry of Antiquities is therefore of the utmost significance testifying to a Greek community living at Hermopolis during the 3rd century BC.